Drivers of landscape change in the Northwest Boreal Region - Sesser, Amanda L., editor; Rockhill, Aimee P., editor; Magness, Dawn R., editor; Reid, Donald, editor; DeLapp, John, editor; Burton, Philip J., editor; Schroff, Eric, editor; Barber, Valerie, editor; Markon, Carl, editor; University of Alaska Press, publisher (Colorado State University. Libraries, 2019)
The Northwest Boreal (NWB) Landscape Conservation Cooperative (LCC) was formed in 2012 to bring together conservation and resource managers in boreal Alaska and northwest Canada with the central purpose of sharing interests and resources to collectively address landscape level issues that are common among resource managers, educators, and the public. As outlined as part of the NWB LCCs strategic plan, this document will provide a foundation by which members of the LCC and other interested parties can find baseline information regarding physical and ecological aspects of the region, as well as potential drivers of landscape change in an area that spans over 1.3 million square kilometers (330 million acres) across Alaska and Canada. This work is the culmination of more than 60 contributing authors engaged in a wide spectrum of study, including physical and biological aspects of the region; natural disturbances; social-ecological drivers; interactions among the natural and anthropogenic characteristics; and engagement among and between scientists and public. This document may well serve as a baseline through which future meaningful engagement with the LCC can take place.--Provided by publisher.
Keywords: Landscape protection -- Alaska; Landscape protection -- Alberta -- Northwest Boreal Region; Environmental protection -- Alaska; Environmental protection -- Alberta -- Northwest Boreal Region; Northwest Boreal Landscape Conservation Cooperative